How skilful are Nowcasting Satellite Applications Facility products for tropical Africa?. (13th November 2020) - Hill, Peter G.; Stein, Thorwald H.M.; Roberts, Alexander J.; Fletcher, Jennifer K.; Marsham, John H.; Groves, James
Abstract: Satellite nowcasting potentially provides a vital opportunity to mitigate against the risks of severe weather in tropical Africa, where population growth and climate change are exposing an ever growing number of people to weather hazards. Numerical weather prediction demonstrates limited skill for much of Africa and weather radars are rare. However, geostationary satellites provide excellent spatial and temporal coverage of the often long‐lasting convective storms that deliver heavy rain, lightning and strong winds, presenting a valuable opportunity for satellite nowcasting. Here, we evaluate the skill of satellite nowcasting products for tropical Africa: these products are routinely generated, but to our best knowledge never routinely used in tropical Africa before the Global Challenges Research Fund African SWIFT (Science for Weather Information and Forecasting Techniques) project. Focusing in particular on convective rainfall rate (CRR) and rapidly developing thunderstorm convection warning (RDT‐CW) products, we demonstrate that both are useful nowcasting tools. The CRR product produces very different rainfall climatologies for day and night in tropical Africa. This is associated with greater skill of the product during daytime, particularly for heavier rain rates. The RDT‐CW product is able to identify around 60% of heavy (>5 mm·hr −1 ) rainfall events with the fraction detected increasing with increasing rainfall rate. For both products, extrapolation forwards in time (up to 90 and 60 min, respectively) maintains useful skill in tropical Africa, motivating work to develop longer lead‐time nowcasts. We conclude that widespread uptake of satellite nowcasting could provide new skilful weather predictions on short time‐scales in much of tropical Africa. Abstract : The weather in tropical Africa has a huge impact on the local population; severe storms often lead to destruction of property and even loss of life. Consequently, improved nowcasting capabilities could bring huge benefits both to the livelihoods of the local populations and to regional economies. In the present study we demonstrate that satellite‐based nowcasting products initially developed for Europe can provide skilful predictions for tropical Africa.